2006
DOI: 10.1021/je060092t
|View full text |Cite
|
Sign up to set email alerts
|

Binary Mutual Diffusion Coefficients of Aqueous Solutions of β-Cyclodextrin at Temperatures from 298.15 to 312.15 K

Abstract: Binary mutual diffusion coefficients (interdiffusion coeffcients) have been measured for aqueous solutions of -cyclodextrin ( -CD) at concentrations from (0.002 to 0.008) mol‚dm -3 . The effect of temperature, from (298.15 to 312.15) K, was also analyzed. The concentration dependence of D is discussed on the basis of Hartley's equation. The activation energy for the diffusion process, 18719 J‚mol -1 , was calculated from data of D at different temperatures. This activation energy is in good agreement with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 34 publications
12
59
1
Order By: Relevance
“…Good reproducibility was observed, as seen by the small standard deviations of the mean, S Dav . Previous papers (Ribeiro, Leaist, et al, 2006;Ribeiro et al, 2008) reporting data obtained with this technique have shown that the error limits of our results should be close to the imprecision, therefore, giving an experimental uncertainty of 1-3%.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Good reproducibility was observed, as seen by the small standard deviations of the mean, S Dav . Previous papers (Ribeiro, Leaist, et al, 2006;Ribeiro et al, 2008) reporting data obtained with this technique have shown that the error limits of our results should be close to the imprecision, therefore, giving an experimental uncertainty of 1-3%.…”
Section: Resultssupporting
confidence: 64%
“…We have been particularly interested in data on these properties for chemical systems occurring eventually in the human organism (Ribeiro et al, 2005;Ribeiro, Leaist, et al, 2006;Ribeiro, Esteso, et al, 2007), having in mind a contribution to better understanding their structure, and supplying the scientific and technological communities with data on these important parameters in solution transport processes, where such data are not currently available. As we are interested in metal ions, such as copper (II), due to their critical role in a variety of biochemical processes (Aldrian, Keen, Lonnerdal, & Dewey, 1997;Ribeiro, Esteso, et al, 2007;YeH, Aloia, Semla, & Chen, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of 1 H NMR self-diffusion of deuterium solutions of CDs shows that, for all three natural CDs, diffusion coefficients depend linearly on the CD volume fraction, suggesting that these molecules are behaving as nonaggregate hard spheres. A similar conclusion was reached from the analysis of the dependence of mutual diffusion coefficients on CDs concentration [58][59][60].…”
Section: Respectivelysupporting
confidence: 78%
“…In fact, in our case, diffusion coefficients for some aqueous CD solutions [12][13][14][15] and caffeine solutions at T = 298.15 K [16] have been reported, but as far as the authors know, after careful literature search, no data are available in literature for ternary systems involving 2-hydroxypropyl-b-cyclodextrin (HP-b-CD) and caffeine molecules for the same concentrations at 298.15 K. Thus, the purpose of this work has been to measure ternary mutual diffusion coefficients (D 11 , D 22 , D 12 , and D 21 ) for T = 298.15 K at carrier concentrations from (0.000 to 0.010) mol Á dm À3 , for each solute, respectively, by using a Taylor dispersion equipment, helping us to better understand the structure of these systems. The description of this technique is well done in the literature [17][18][19][20][21][22][23], and consequently we only report a summary concerning the experimental procedure.…”
Section: Introductionmentioning
confidence: 70%